STRATEGI KOMUNIKASI PENGASUH PONDOK DALAM PEMBINAAN AKHLAK SANTRI - Azizah Choirun Nikmah; Henny Yusnita (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2020)
In Indonesia there are many Islamic religious institutions, which are due to the Islamic majority of Indonesians. In the sambas district there is also the Islamic institution of education that has existed since 1979, the reformatory of Muhammad Basiuni Imran (PPMBI) sambas district. The purpose of this study is to learn about communication strategies used by PPMBI caregiver to morticizing santri. The approach used was peddlers sociological. The kind of research used in this study is qualitative. The data-collection techniques used in this study are observation, interviews, and documentation. These research data analysis techniques are data reduction, data display, and verification or conclusions. Whereas the authentication technique used by researchers was the data triangulation and the crew check. Research is based on the strategy that non-commissioned nurses of PPMBI engage in moral policing is persuasion in form of santri, method, attention, dialog or question-and-answer, and rule models.